Anthropological theory today - Moore, Henrietta L. (Cambridge : Polity Press, 1999)
This important book makes a bold statement about the nature and value of anthropological theory at the beginning of the 21st century. It repositions anthropology within current social theory and outlines the changing context in which anthropological enquiry takes place. Anthropology is no longer confined to academic debate and is increasingly part of the practice and theory of development agencies, voluntary organizations, political pressure groups, international organizations and governments. Anthropological theory has become less and less isolated from the communities studied. Communities are increasingly culturally diverse, and 'other cultures' are no longer in 'other parts' of the world. The essays in this volume develop new ways of theorizing appropriate to these changed circumstances.The authors rework the role of the anthropologist in knowledge construction to provide a critique of the working concepts and assumptions of disciplinary theory and practice. The contributions highlight questions of power, domination and discrimination in ways that illuminate current ethical dilemmas in anthropology. Key concept-metaphors - the self, the body, and gender - are subjected to critical assessment, and questions of diversity, agency and representation are given renewed emphasis. The book demonstrates the continuing importance of ethnography to the development of theoretical work in the discipline, and provides new answers to the question 'What is anthropology?' This book will be essential reading for all students of anthropology. It will also be of interest to students and scholars in sociology, history and related disciplines.
Anthropological theory at the turn of the century / Henrietta L. Moore -- From private virtue to public vice / James G. Carrier and Daniel Miller -- Clash of civilizations or Asian liberalism? : an anthropology of the state and citizenship / Aihwa Ong -- The economics of violence and the violence of economics / Catherine Lutz and Donald Nonini -- Toward an ethics of the open subject : writing culture in good conscience / Debbora Battaglia -- Whatever happened to women and men? : gender and other crises in anthropology / Henrietta L. Moore -- The body's career in anthropology / Thomas J. Csordas -- Human cognition and cultural evolution / Pascal Boyer -- Psychoanalysis and anthropology : on the temporality of analysis / James Weiner -- Becoming undisciplined : anthropology and cultural studies / Nicholas Thomas.
Lisäpainokset: Repr. 2000. - Repr. 2003.
Keywords: Anthropology -- Philosophy; Ethnology -- Philosophy; väkivalta; kulttuuriantropologia; antropologia; teoriat; filosofinen antropologia; sukupuoliroolit; ruumiinkuva; kognitiivinen antropologia; psykoanalyysi; kulttuurintutkimus; valtio (instituutio); kansalaisuus; ruumiinkuva -- kulttuuriantropologia; valtio -- kansalaisuus -- kulttuuriantropologia; väkivalta -- kulttuuriantropologia; sukupuoliroolit -- kulttuuriantropologia; kulttuuriantropologia -- teoriat; kulttuuriantropologia -- psykoanalyysi; kulttuurintutkimus -- antropologia; valtio -- kansalaisuus